Estandarización del proceso de producción de carbón activado por activación física a partir de cuesco de palma a escala industrial (2017)
Activated carbon is a carbonaceous material product of thermal decomposition of materials with a high carbon content in its structure, it functions as an adsorbent and presents a different field of application in the industrial sector, implemented for: water treatment, recovery of solvents, sugar industry, mining, and others. For the development of this project is a carbon produced at an industrial level from the palm shell, considering that it is a material with optimal characteristics to be used as a precursor to activated carbon. It was taken into account the abundance of the waste generated in the palm sector, supply its collection and propagation in an appropriate management, taking into account the volumes of waste produced, cause some environmental and social problems. During the process of production of activated carbon, in the carbonization and activation, the temperature and time of residence will be evaluated as critical variables of the process, to establish their influence on the properties of the product obtained. In addition, it establishes the optimal operating conditions for obtaining an activated carbon with uniform characteristics, offering a product that compete in the market with activated carbon from other industries.